Information System Development for Web-Based Creative Services E-Commerce Using Rapid Application Development Method - Bagus Dwi Putra Adiyono; Abdul Rezha Efrat Najaf; Reisa Permatasari (bit-Tech, 2025)
This study aims to design and develop a web-based e-commerce information system for creative services at Cahaya Kreativ using the Rapid Application Development (RAD) method, addressing the company's lack of an integrated digital platform for managing service orders, portfolios, consultations, and online payments. The RAD method was chosen due to its emphasis on speed, prototyping, and close user collaboration—making it more suitable than traditional methods like Waterfall for projects requiring rapid development and ongoing user input in a dynamic service environment. The system was built using React.js for the frontend, Express.js for the backend, PostgreSQL as the database, Tailwind CSS for UI design, and Midtrans integration as a payment gateway. The development process included two iterations covering requirement analysis, system design (use case diagram, sequence diagram, class diagram, ERD), implementation, and testing through Blackbox Testing and User Acceptance Testing (UAT). Results indicate that the system operates according to specifications and has received positive user feedback. It is expected to enhance Cahaya Kreativ’s operational efficiency, expand market reach, and improve the digital experience for customers ordering creative services online, while also supporting streamlined business processes, data consistency, and increased user engagement through responsive and interactive features. Stakeholder involvement throughout the development ensured the system closely matched real business requirements, resulting in a comprehensive digital solution that enhances customer satisfaction and operational performance through technology-driven innovation.